Identification of approaches to architectural and structural solutions in the design of sports buildings (Nexo Revista Científica, 2022)
In the modern world, sports facilities are multifunctional complexes that not only meet the needs of the sports infrastructure but also serve as recreational facilities. Sports buildings and facilities are constructed using large-span structures and require significant urban areas for their erection. The paper discusses the results of research carried out by the Moscow State University of Civil Engineering, which provides for the efficient use of the building area of sports facilities and the reduction of the cost of facilities through the use of space within the large-span structures for the placement of a large number of sports infrastructure facilities. The key issue in solving the problem of compactness of the developed area is the use of large-span structures of intermediate floors. Based on the selected cases, the authors classify approaches in the design of sports buildings, based on the use of three types of large-span floor structures: steel-reinforced concrete floor slab, load-bearing floor, and building-bridge. The authors conclude that these approaches can be used in the design of various types of sports facilities: from the municipal level of sports and recreation complexes to facilities designed for major international competitions.